Kegiatan Formative Research Pt.Kai (Persero) dalam Upaya Sosialisasi Pintu Keselamatan oleh Humas Daop 2 Bandung - Nurpijar Kaloka, Hanas; Damayanti, Trie; Ruchiat Nugraha, Aat (Institut Hindu Dharma Denpasar, 2018)
This study aims to determine the activities formative research conducted by the Public Relations Daop 2 Bandung covering the analysis of the situation, organizations and the public.The method used is descriptive exploratory method to be more profound and accurate with qualitative data.The results of this study is the first phase of the analysis of the situation that has been done by the PR Daop 2 Bandung has implemented properly guided by several indicators that the analysis of the situation is reached plus has been working with Edan Community railroad Indonesia (Kesi).However, analysis of the situation which has been run by the Public Relations have several indicators or elements that are less maximized on the deepening of the data and facts and resulted in a lack of accurate analysis of the public in the third stage in the formative activities of this research. Analysis of the organization that has been built and observed by the Public Relations have also given an overview of how the organization in this company is running but some internal activities are still not able to be implemented with maximum coordination as its terms of internal meetings. Suggestions for Public Relations Daop 2 Bandung to keep attention to detail more than any analysis of the formative research in order to provide maximum results in a program or activity on the socialization of planning safety doors in Daop 2 Bandung. Formative research as one of the PR concept will be very helpful for PR practitioners in order to pay attention to research for the attainment of maximum activity or program.